Effects of span-depth ratios on the energy release rate for three-point bending beams. (1st March 2021) - Yin, Yangyang; Hu, Shaowei
Highlights: Expressions for the energy release rate for TPB specimens with various span-depth ratios were developed. Double- G fracture parameters were obtained. Equivalence between double- G and double- K fracture model was revealed. The analytical and experimental results of G I c un exhibit a good consistency. The analytically obtained G I c un was insensitive to the softening function. Abstract: The effects of span-depth ratios on the energy release rate for three-point bending beams were examined. Expressions for the energy release rate for three-point bending specimens with various span-depth ratios were developed using linear interpolation method. The double- G fracture parameters were calculated through tests of three-point bending beams with the same span (800 mm) but various depths (100 mm, 150 mm, 200 mm, 250 mm and 300 mm) and the findings in literature. Results indicate that (1) with increasing the span-depth ratio, an almost constant initial fracture energy release rate was obtained, and slight decrease tendency of the unstable energy release rate was observed; (2) The empirical relationship between the initial fracture energy and total fracture energy suggested in size effect model was conformed using the unstable fracture energy release rate which was the same as the initial fracture energy; (3) Equivalence between double- G and double- K fracture model was verified; (4) Moreover, the analytical results of unstable fracture energy release rate exhibited a good consistency with the experimental ones, which were insensitive to the softening function.